Analisis Dampak Struktur Modal Terhadap Profitabilitas - Dwi Setiarini; Sujiono Sujiono; Hadi Sumarsono (Universitas Muhammadiyah Ponorogo, 2018)
Funding is an important issue that is taken into account by the company, both for the establishment and expansion of the business. Capital structure has an impact on profitability, with the improvement in capital structure, the company gives profits. The purpose of this study was to determine the impact of the capital structure measured by Debt to Equity Ratio (DER) on profitability as measured by Return on Assets (ROA) partially in Sharia Savings and Credit Cooperatives Cooperatives or KSK Komment Year 2016 - 2019. This researcher uses regression analysis simple linear and t test. The data source used in this study is secondary data. The results of the study concluded that the capital structure measured by Debt to Equity Ratio (DER) partially had a negative impact on Return on Assets (ROA). While the t test on the variable Debt to Equity Ratio (DER) partially proved to have no significant impact on Return on Assets (ROA).